Penerapan Metode Drill Untuk Meningkatkan Penguasaan Hafalan Kosa Kata Bahasa Arab Siswa Kelas VII - Masfiyatul Asriyah; Rahmawati, Rima Ajeng (An Naba, 2021)
Drill method is a learning method by giving practice in a creative and continuous way. This study aimed to describe the improvement of Arabic vocabulary memorization using the Drill method and the application of the drill method for seventh grade junior high school students. This type of research is classroom action research with a descriptive quantitative approach. This research was carried out in two cycles, consisting of eight meetings in seventh grade SMP Muhammadiyah I Bandar Lampung in the 2019/2020 academic year. The subjects used in this study were 17 students. Based on the results of the research that has been done, it can be concluded that the Drill method can improve the vocabulary memorization of seventh grade Muhammadiyah Middle School students. This is evidenced by the increase from cycle I to cycle II. In addition, students become more disciplined and active in learning Arabic with the drill method. Based on these results, it can be concluded that the Drill method is one of the solutions to be applied in overcoming difficulties in memorizing Arabic vocabulary.